REDES DE APOIO SOCIAL E QUALIDADE DE VIDA EM HOMENS IDOSOS DE SÃO CAETANO DO SUL - Santos, Daniel de Oliveira (2006)
This study object, to identify the partner-demographic characteristics of a men senior group of inhabitants who live in the City of São Caetano do Sul, and the main nets of social support among those senior people, investigating the level of quality of life of them. The data were picked up between October 2005 and March 2006. The sampling was obtained by an interview of 40 men; all of them were male, with medium age around 70, 68 years old. This sample was compound by 20 people who were interviewed in The Center of Coexistence (CC) for the third age and 20 were interviewed in the streets and Parks around the City of São Caetano do Sul. Two questionnaires were used being one about Social Support Net and another structured specifically about quality of life, the WHOQOL bref. At the end of the questionnaires two new subjects were included to investigate the providences took about the old people and how they spend their money in the old age. The comparison among those two sub-groups allowed us to verify that those CC seniors members, revealed the largest participation in group activities (p <0, 05) and the largest frequency in weekly sporting practice (p <0, 01). In subjects about situations where people seek for others, mainly for a kind of relationship, support or for helping, those seniors who don't take part of CC obtained better results (p <0, 05), so that, they really are privileged who could count with others to share theirs concerns and the most private fears (p <0, 05). Divorced seniors tend to count with others who help them if they need to stay in bed for any reason (p <0, 05) more than senior widowers who have a more possibility to getting help in case to prepare its food, and also in case of getting sick than the senior widowers (p <0, 01). It was possible to observe in the samples, that there are more incidences of senior widowers and divorced ones to take part of CC as well as it was verified that some samples showed The Social Net be more defective . However, it was observed a better quality of life in samples among those seniors when questions was answered by seniors who was interviewed in the streets (p <0, 05). We conclude that the participation of seniors in The CC, can help strongly for improvement of the quality of life, due to sporting activities, social events and the infrastructure offered for the third age